2019
DOI: 10.1039/c9cp00897g
|View full text |Cite
|
Sign up to set email alerts
|

Effects of temperature and pressure on the optical and vibrational properties of thermoelectric SnSe

Abstract: We have conducted a comprehensive investigation of the optical and vibrational properties of the binary semiconductor SnSe as a function of temperature and pressure by means of experimental and ab initio probes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 90 publications
(206 reference statements)
1
16
0
Order By: Relevance
“…For both samples, the semimetallic high-pressure phase originates from a change in the atomic coordinate z of the Sn atom along the c axis. Although the sample remains in the Pnma space group 31,34,47 , the c axis shows more drastic compression than the other axes 47 . In particular, within the scope of the calculations, only adjusting the lattice parameter does not lead to a metallic phase, even up to 10 GPa.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…For both samples, the semimetallic high-pressure phase originates from a change in the atomic coordinate z of the Sn atom along the c axis. Although the sample remains in the Pnma space group 31,34,47 , the c axis shows more drastic compression than the other axes 47 . In particular, within the scope of the calculations, only adjusting the lattice parameter does not lead to a metallic phase, even up to 10 GPa.…”
Section: Discussionmentioning
confidence: 97%
“…At 0.86 GPa, the compound transforms from a two-valley system to a four-valley system, accompanied by improved thermoelectric properties, providing proof that pressure is a powerful tool to tune the electronic multivalley 27,28 . Densityfunctional theory (DFT) calculations and transport studies have reported enhanced thermoelectric properties of SnSe upon application of external pressure [29][30][31][32] . Although transport measurements 33,34 and theoretical approaches 35,36 provide evidence for a semiconductor-semimetal transition, direct investigations of the electronic structure and its pressure dependence are still lacking.…”
Section: Introductionmentioning
confidence: 99%
“…Sn/Se vacancies can significantly improve S 2 σ by tuning n / p to their optimized values, which can be explained and guided by the variation of their band structures 207,213,234,268,269,272–298. Taking Sn vacancy for example, Figure 7c,d compares the calculated band structures for SnSe and Sn 1− x Se (here x = 0.008 is used), respectively, and Figure 7e compares DOS based on DFT calculations 197.…”
Section: Vacancy Engineeringmentioning
confidence: 94%
“…Due to the excellent electronic and optical properties of binary compounds in transition metals, many scholars have conducted in-depth research in photovoltaic and solar-cell systems. [1][2][3][4][5] Among binary compounds in transition metals, SnSe has great application prospects because SnSe has an orthorhombic crystal structure, 6 which is suitable for solar cells. SnSe is a p-type semiconductor and its high absorption coefficient (10 5 cm À1 ) ensures that solar radiation is absorbed almost completely.…”
Section: Introductionmentioning
confidence: 99%